Pengaruh Kepemimpinan, Status Kepegawaian dan Kompensasi terhadap Orgazational Citizenship Behaviour (OCB) pada Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) di Kota Pariaman - Jabar, Syabran; Putri, Nora Eka (JESS (Journal of Education on Social Science); Vol 10 No 2 (2026): Public Participation in Public ServiceDO - 10.24036/jess.v10i2.677, 2026)
This study aimed to analyze the influence of leadership, employment status, and compensation on Organizational Citizenship Behaviour (OCB) among PPPK employees within the Pariaman City Government. The study employed a quantitative approach with an associative research design. The respondents consisted of 250 PPPK employees distributed across various Regional Government Organizations (Organisasi Perangkat Daerah/OPD) in Pariaman City. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, classical assumption tests were conducted, including tests of normality, multicollinearity, and heteroscedasticity.   The results showed that leadership had a positive and significant effect on Organizational Citizenship Behaviour (OCB). Employment status also had a positive and significant effect and was identified as the most dominant variable influencing OCB. Meanwhile, compensation did not have a significant effect on OCB. Simultaneously, leadership, employment status, and compensation significantly influenced Organizational Citizenship Behaviour (OCB). The findings indicate that voluntary work behaviour among PPPK employees is more strongly influenced by leadership factors and clarity of employment status than by financial factors. Therefore, efforts to improve OCB among PPPK employees should focus on strengthening leadership quality and managing employment status more effectively.